PENGARUH BEBAN KERJA, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA ( Studi kasus Pada Dinas Lingkungan Hidup Kota Malang ) - Nurdina Andriani; Hadi Sunaryo; M Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was conducted to determine how much influence the variable workload, work motivation, and work discipline on employee performance. Malang City Environmental Service Study. In this study the population numbered 68 people using random sampling. The method of taking samples is, employees who work at the Department of Environment of Malang City. To find out the data that will be examined later, this study uses a way to distribute questionnaires to better know the opinions of employees by filling out the statements that have been attached to the questionnaire.In addition, this study uses the SPSS measuring instrument to test data in the form of instrument testing, multiple linear regression analysis, classical assumption testing, and hypothesis testing. This research resulted in several conclusions which stated that the variables of workload, work motivation, and work discipline were simultaneously influential so that they could improve the performance of the employees of the Malang City Environmental Service. While partially workload has a significant effect on employee performance, motivation has a significant effect on employee performance and work discipline has a significant effect on employee performance. Keywords: Effect of Workload, Work Motivation, and Work Discipline on Employee Performance